(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
This article discusses the types and classifications of lacunae. Each of the considered types and classifications is used to describe the differences between languages and cultures in a certain aspect. In addition to the fact that they are active words of this dialect, they are of great importance for enriching the vocabulary of the literary language